Comparing transcriptomes of distant organisms: the comparative ENCODE resource 1 - Gerstein, Mark (Henry Stewart Talks, 2017)
Comparative ENCODE functional genomics resource, Non coding transcription, Transcriptionally active regions (TARs), Machine learning models for un-annotated transcription, Expression clustering, cross-species, Developmental 'hourglass' genes